Food security management in developing countries: Influence of economic factors on their food availability and access. - Norbert Bozsik; Julieth P Cubillos T; Bopushev Stalbek; László Vasa; Róbert Magda (PLoS ONE)
The research presents an analysis of the food security policy effectiveness on the component of food availability and access in two developing countries, Colombia and Kyrgyzstan, during the period from 2000 to 2018. Determining the state of their food balance trade and the regression analysis for the Food Production Index of the countries, considering four economic indicators. Thus the study attempts to show that policies and strategies have not reached the expected results in terms of reduction of food imports dependency and strengthening of national production and export industry. Furthermore was found that among the economic indicators considered, food inflation, food imports, food exports, and extreme monetary poverty; the last one was the indicator that presented influence on the Food Production Index of both countries, during the period analyzed, showing that access was the main component that defines the food production. The results highlighted the need of integrating food security with the monetary and trade policies of these countries.